Diagnosis and Management of Patients with Heart Failure with Preserved Ejection Fraction (HFpEF): Current Perspectives and Recommendations - Dzhioeva O; Belyavskiy E (Dove Medical Press, 2020)
Olga Dzhioeva,1 Evgeny Belyavskiy2 1Department of Fundamental and Applied Aspects of Obesity, National Medical Research Center for Preventive Medicine of the Ministry of Health of the Russian Federation, Moscow, Russia; 2Department of Internal Medicine and Cardiology, Charité - Universitätsmedizin Berlin, Berlin, GermanyCorrespondence: Evgeny BelyavskiyDepartment of Internal Medicine and Cardiology, Charité – Universitätsmedizin Berlin, Campus Virchow Klinikum Augustenburger Platz 1, Berlin 13353, GermanyTel +49 30450565494Fax +49 304507565494Email evgeny.belyavskiy@charite.deAbstract: Heart failure with preserved ejection fraction (HFpEF) is a major global public health problem. Diagnosis of HFpEF is still challenging and built based on the comprehensive echocardiographic analysis. Currently, there are no universally accepted therapies that alter the clinical course of HFpEF. This review attempts to summarize the current advances in the diagnosis of HFpEF and provide future directions of the patients´ management with this very widespread, heterogeneous clinical syndrome.Keywords: heart failure with preserved ejection fraction, transthoracic echocardiography, guidelines, diastolic stress test